Evaluasi Usability Virtual Classroom Multi-user Menggunakan Metode GUESS - Secondio Prawiro; I Kadek Dendy Senapartha; Matahari Bhakti Nendya (Jurnal Terapan Teknologi Informasi, 2026)
This study aims to evaluate the usability and effectiveness of a Virtual Reality (VR)-based Multi-User Virtual Classroom as an alternative medium for learning Newton's Laws. The system facilitates real-time 3D object manipulation and multi-user interaction. The evaluation involved 31 high school students divided into three testing platforms: VR, Desktop (PC), and Mobile. Usability was measured using the Game User Experience Satisfaction Scale (GUESS), while learning effectiveness was assessed using Pre-Test/Post-Test methods and comparative platform analysis. Descriptive analysis based on user perception surveys indicates that the VR platform yielded the highest effectiveness trend, with an average approval score of 83.3% calculated across conceptual understanding, interaction quality, and practice quality aspects. In contrast, the Desktop platform scored 60%, and the Mobile platform scored the lowest at 50% due to control limitations and lack of immersion. Furthermore, Pre-Test and Post-Test data confirmed a significant improvement in conceptual understanding and correction of misconceptions. It is concluded that the VR-based Virtual Classroom is the most effective solution for overcoming interaction limitations in online learning compared to non-immersive platforms.